2010
DOI: 10.4047/jap.2010.2.2.33
|View full text |Cite
|
Sign up to set email alerts
|

Influence of porcelain veneering on the marginal fit of Digident and Lava CAD/CAM zirconia ceramic crowns

Abstract: PURPOSEMarginal fit is a very important factor considering the restoration's long-term success. However, adding porcelain to copings can cause distortion and lead to an inadequate fit which exposes more luting material to the oral environment and causes secondary caries. The purpose of this study was to compare the marginal fit of 2 different all-ceramic crown systems before and after porcelain veneering. This study was also intended to verify the marginal fit of crowns originated from green machining of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 17 publications
3
84
0
8
Order By: Relevance
“…For the manual adapted copings, the mean marginal gaps varied from 54 to 59.9 μm. This is in accordance with marginal gaps reported for CAD/ CAM-generated zirconia copings in other studies, in which marginal gaps ranged from 24 to 110 μm 6,11,14,15,31) . The large variation in the reported mean values can be explained by a number of infl uencing factors, including CAD/CAM components and differences between presintered and post-sintered milling of the zirconia blank.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…For the manual adapted copings, the mean marginal gaps varied from 54 to 59.9 μm. This is in accordance with marginal gaps reported for CAD/ CAM-generated zirconia copings in other studies, in which marginal gaps ranged from 24 to 110 μm 6,11,14,15,31) . The large variation in the reported mean values can be explained by a number of infl uencing factors, including CAD/CAM components and differences between presintered and post-sintered milling of the zirconia blank.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that allceramic crowns show a mean marginal discrepancy that ranges from 19-160 μm [7][8][9][10] . The mean marginal gap for CAD/CAM-generated crowns is reported to be 23-110 μm 6,[11][12][13][14][15] . Many authors accept the criterion established by McLean and von Fraunhofer (1971) who proposed after a 5-year examination of 1,000 restorations that 120 μm should be considered the maximum marginal gap 6,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique reduces processing errors that may be associated with conventional sintering and has been shown to improve mechanical stability 21,22) . Marginal fit is an important factor in the success of restorations 23,24) . Marginal fit is related to both vertical and horizontal discrepancies.…”
Section: Introductionmentioning
confidence: 99%